Development of conceptual framework for cyber fraud investigation - Hidayati, Anisa Nur; Riadi, Imam; Ramadhani, Erika; Al Amany, Sarah Ulfah (Information Systems - Universitas Pesantren Tinggi Darul Ulum, 2021)
The increase in the number of internet users in Indonesia as much as 175.4 million as recorded in the Datareportal.com report and 4.83 billion globally, impact the increase in the number of cyber fraud cases. Data states that 96% of fraud cases are not resolved due to fraud methods carried out online and make it difficult for legal officers to obtain evidence. Previous fraud investigation research mainly focused on fraud detection, so this research focuses on submitting a framework for investigating cyber fraud cases. The cyber fraud case requires a new framework for investigation because in this fraud case, there is digital evidence that is very prone to be damaged, lost, or modified, which makes this case unsolved. This research aims to develop a framework that is expected to help auditors to uncover cases of cyber fraud so that resolved cyber fraud cases can increase. The method used in making this framework uses Jabareen's conceptual framework development method, which consists of 6 stages, namely, Mapping the selected data source, extensive reading and categorizing of the chosen data, Identifying and naming objects, Deconstructing and categorizing the concept, Integrating concept, Synthesis, resynthesis. And make it all sense. The framework for cyber fraud investigation uses 22 digital forensic frameworks and eight frameworks for fraud audit investigations. The results of developing a framework using the Jabareen method resulted in 8 stages, integrating various concepts selected from digital forensics and fraud audits. Evaluation of framework development was carried out by giving limited questionnaires to practitioners and academics, which produced 89% for the feasibility value and needs of the framework and 67% there is no need for changes to the framework being developed.